PENDEKATAN ISLAMI DALAM PENDIDIKAN ANAK USIA DINI BERDASARKAN AJARAN NABI MUHAMMAD SAW - Abbas, Ngatmin; Astoko, Dudi Budi (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2024)
Early childhood education (ECE) based on Islamic principles offers an approach that can bridge the gap between traditional and modern education. Principles from the teachings of Prophet Muhammad SAW, such as role modeling, compassion, and discipline, are foundational in educating children. However, integrating these principles into an ECE curriculum that meets academic standards and developmental needs in the modern era remains a challenge. This study aims to explore effective ways to adapt Islamic educational principles into an ECE curriculum that fulfills academic standards while supporting the development of character and moral values in children. This research employs a qualitative approach with a library research method to analyze relevant literature on Islamic education and ECE curriculum. Data were collected from academic sources, hadiths, and Islamic educational guidelines to identify the implementation of Prophet’s teachings in a modern context. The research indicates that integrating moral and spiritual values into the ECE curriculum enhances character and moral development in children. Methods involving educator role modeling, reinforcement of compassion, and application of supportive discipline, along with the use of technology and appropriate educational materials, are effective in creating a supportive learning environment. This adaptation also includes training for educators and curriculum development that aligns with local and cultural needs.